已知f(x)=2^x-2^-x,g(x)=2^x+2^-x
f(x)*f(y)=4,g(x)*g(y)=8,求g(x+y)/g(x-y).
汗... 我看着答案都不知道怎么解的... 最好加我Q 947384033
已知f(x)=2^x-2^-x,g(x)=2^x+2^-x
f(x)*f(y)=4,g(x)*g(y)=8,求g(x+y)/g(x-y).
汗... 我看着答案都不知道怎么解的... 最好加我Q 947384033
f(x)*f(y)=(2^x-2^-x)*(2^y-2^-y)=2^(x+y)-2^(y-x)-2^(x-y)+2^(-x-y)=4……(1)
g(x)*g(y)=(2^x+2^-x)*(2^y+2^-y)=2^(x+y)+2^(y-x)+2^(x-y)+2^(-x-y)=8……(2)
(1)-(2)得到2*2^(y-x)+2*(x-y)=4亦即2^(y-x)+2^(x-y)=4
(1)+(2)得到2*2^(x+y)+2*2^(-x-y)=12亦即2^(x+y)+2^(-x-y)=6
g(x+y)/g(x-y)=2^(x+y)+2^(-x-y)/2^(x-y)+2^(-x+y)
=6/4=3/2
[刚才我是真的忙,不好意思了!]